Policies for Brazilian Distance Higher Education: Challenges of Expansion - Haas, Celia María; Moutinho Neves, Lidiane; De Paula Stander, Marcus Danilo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
The text focuses on national policies for Distance Higher Education (DHE) and aims to analyze the trajectory of policies under this modality and to reflect on the challenges that its growth poses for ensuring the quality of education. It is a documentary and bibliographic research, supported by a careful search of the legislation that rules and organizes the offer of distance higher education in Brazil, complemented by a careful review of the literature from authors who discuss the subject. The DHE regulation at the national level was consolidated with the approval of Federal Law No. 9.394 of December 20, 1996, Ley de Directrices y Bases de la Educación Nacional –LDBEN- (law on guidelines and bases of national education), giving way to a period of incentive for the implementation of this modality. In 2017, Federal Decree No. 9.057 of 25 May, supplemented by Portaria Regulation No. 11 of 20 June 2017, significantly altered the legislation and standardization of the Brazilian DHE with a strong favoring towards the accelerated expansion of distance higher education. Brazil has considerable challenges to be faced with regard to DHE, among which the quality of the education offer stands out, including service provision, access and permanence of students in higher education, the use of digital technologies and the expansion of this modality.